Health behaviour change : a guide for practitioners - Rollnick, Stephen; Mason, Pip; Butler, Christopher (Churchill Livingstone, 2002)
(Churchill Livingstone) Univ. of Wales, Cardiff, UK. Presents method that will assist health professionals in helping their patients make decisions about health behavior change in the hospital and community settings. Applicable to any behavior, including over-eating, physical inactivity, smoking, diabetes, and heart disease. Softcover.
Keywords: zdravé chování; Health Behavior